Impact of TP53 mutations on the efficacy of CAR-T cell therapy in cancer - Regina Mirgayazova; Raniya Khadiullina; Maria Filimonova; Vitaly Chasov; Emil Bulatov (Exploration of Immunology)
The efficacy of chimeric antigen receptor (CAR)-T therapy may not match initial expectations due to the influence of multiple circumstances, some of which cannot be predicted. CAR-T treatment groups include high-risk patients, particularly those with TP53 mutations. A significant body of research has demonstrated that mutations in the TP53 gene play a pivotal role in cancer development and progression. Any aberration in the TP53 gene in cancer is invariably associated with complications and a poor prognosis. Moreover, mutations in the TP53 gene have been observed to correlate with resistance to conventional chemotherapy, prompting the use of alternative therapeutic approaches, including CAR-T therapy. However, there is a possibility that abnormalities in the TP53 gene may affect patients after CAR-T cell administration reducing the efficacy of therapy. This review examines the link between TP53 mutations in cancer and the efficacy of CAR-T therapy, as well as the potential implications of this aspect in therapeutic planning.